Evaluating the strengthening effect of combined amalgam-composite restoration on the weakened wall of a dental cavity: An in vitro study - Syed Nahid Basheer (Wolters Kluwer Medknow Publications, 2015)
Background: Combined amalgam-composite restoration capitalizes on the advantageous properties of the two materials and nullifies their individual disadvantages. Aim: This in vitro study was conducted to evaluate the strengthening effect of combined amalgam-composite restoration on the weakened wall of a dental cavity by measuring the cuspal deflection. Materials and Methods: Ten human maxillary premolar teeth with similar crown size were selected. Each tooth was subjected to a respective procedure and tested in the following sequence: Group 1 (sound teeth), Group 2 (cavity-prepared teeth), Group 3 (amalgam-restored teeth), Group 4 (amalgam-removed teeth), and Group 5 (amalgam-composite restored teeth). The cuspal deflection was measured using strain-gauge methodology. Statistical Analysis: ANOVA test and Bonferroni test for multiple comparisons were used. The level of significance was fixed at P < 0.05. Results: The mean cuspal deflection and standard deviation values recorded for buccal cusps of each of the five groups respectively were: 28.70 (8.88), 112.03 (55.93), 86.56 (40.77), 120.50 (59.03) and 59.40 (32.10) and for lingual cusps were: 118.00 (37.46), 178.80 (50.86), 147.47 (47.76), 185.33 (48.29), 151.03 (46.11). A significant difference in the cuspal deflection between the groups with respect to the buccal cusp (P < 0.001) and lingual cusp (P < 0.01) respectively was noted. However, as compared to sound teeth, there was no significant recovery of lost strength in amalgam-restored as well as in amalgam-composite restored teeth. Conclusion: The combination restorative technique cannot be relied upon to reinforce unsupported enamel to a level similar to that provided by dentin.